Pendampingan kepada Guru dalam Penyusunan Pedoman Penguatan Soft Skill Kesiapan Kerja bagi Siswa SMK Nasional - Esti Setiawati; Palupi Sri Wijayanti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this service activity is to develop soft skill guidelines for work readiness for vocational students. The target of this service is adaptive and productive teachers. The target to be achieved from vocational school teachers is the realization of a soft skill development manual for students in preparing for work. This service activity took a place in the National Vocational School of Berbah,Â Sleman regency with all active teachers as participants. The stages of service activities carried out were 1) preparation as a form of administrative completeness before carrying out activities, 2) implementation carried out with an active learning approach (activity, analysis, abstraction, and application), 3) closing by evaluating the ability to understand soft skills concepts and rubrics soft skills assessment. The result of this service activity showed that the level of understanding and competence of teachers' knowledge related to soft skills from the concept aspect and the assessment rubric was very good. Based on these capabilities, the outputs and answers to partner problems were answered by the compilation of a soft skill manual for students of the Berbah National Vocational School in Sleman regency in the face of competition in the world of work.